Cognitive-epistemological, pragmatic, and psycholinguistic aspects of French interjections - Khaichevska, Tetiana; Bondaruk, Liudmyla; Rohach, Oksana (East European Journal of Psycholinguistics, 2024)
Interjections as a lexical and grammatical category still belong to the interdisciplinary lacunae, as they require the concretization of interpretations in various aspects: terminological definitions, pragmatic functions, cognitive reception by a speaker, and an adequate reproduction by an addressee. The current study aims to analyze the determinative interpretations and lexical and grammatical structures of interjections as a universal category used for determining communicative and pragmatic functions. A part of the psychological epic In Search of Lost Time/“A la recherche du temps perdu” – Albertine Disappears / “Albertine Disparue”) by Marcel Proust (1925) serves as a research material. Interjections, as a universal category, hold a prominent place in the lexical and grammatical system of languages. As a result of conducted quantitative analysis of interjections, the most common interjections discovered in the studied literary French-language text were one-word interjections, ‘oh!’ ‘ah!’, and ‘hélas!’, which, depending on the author’s illocutionary intention, their pragmatic function, as well as their position in the remark - at the beginning, in the middle or at the end - can create a range of meanings according to their emotional effect, such as hope, disappointment, doubt, embarrassment, confirmation, denial, request or call to action. Conversely, the texts frequently comprise interjection phrases that convey the processes of reflection on the inner experiences of a particular character and their psychological state. This, in turn, reveals the process of their personality development. Disclosure Statement The authors reported no potential conflicts of interest. * Corresponding author: Oksana Rohach, 0000-0002-5304-0837oksanarog@vnu.edu.ua